Teachers' perceptions of assessment for learning (AfL) - Ko, Ai Boi (Universiti Malaysia Sarawak (UNIMAS), 2015)
Assessment for Leaming (AfL) is a worldwide initiative which is promoted to improve student learning. AfL refers to the process of seeking and interpreting evidence for use by learners and their teachers to decide where the learners are in their learning. As AfL is a relatively new pedagogical approach in Malaysia, this study aimed to investigated the secondary school teachers' perceptions of Assessment for Learning (AfL). The influence of demographic factors such as gender and teaching experiences on teachers' perceptions were also investigated. The research design used in the study was a Cross-Sectional Survey with descriptive and parametric statistical analyses. The samples in this study consisted of 96 teachers in three Malaysian Government secondary school in Sarawak, who had been trained with the AfL strategies. Independent t-test and one-way ANOVA test were used to determine the differences in teachers' perceptions of AfL based on gender and teaching experiences. The findings of this study showed that the teachers generally had positive perceptions of AfL. The study also found that there were no differences in teachers' perception based on gender and teaching experiences. The findings of these results provide insights into enhancing teachers' perceptions ofAfL and their AfL practices in classroom.